The critical role of persistent sodium current in hippocampal gamma oscillations - Kang, Young-Jin (Neuropharmacology, 2019)
Gamma network oscillations in the brain are fast rhythmic network oscillations in the gamma frequency range (~30-100 Hz), playing key roles in the hippocampus for learning, memory, and spatial processing. There is evidence indicating that GABAergic interneurons, including parvalbumin-expressing basket cells (PVBCs), contribute to cortical gamma oscillations through synaptic interactions with excitatory cells. However, the molecular, cellular, and circuit underpinnings underlying generation and maintenance of cortical gamma oscillations are largely elusive. Recent studies demonstrated that intrinsic and synaptic properties of GABAergic interneurons and excitatory cells are regulated by a slowly inactivating or non-inactivating sodium current (i.e., persistent sodium current, I(NaP)), suggesting that I(NaP) is involved in gamma oscillations. Here, we tested whether I(NaP) plays a role in hippocampal gamma oscillations using pharmacological, optogenetic, and electrophysiological approaches. We found that I(NaP) blockers, phenytoin (40 μM and 100 μM) and riluzole (10 μM), reduced gamma oscillations induced by optogenetic stimulation of CaMKII-expressing cells in CA1 networks. Whole-cell patch-clamp recordings further demonstrated that phenytoin (100 μM) reduced I(NaP) and firing frequencies in both PVBCs and pyramidal cells without altering threshold and amplitude of action potentials, but increased rheobase in both cell types. These results suggest that I(NaP) in pyramidal cells and PVBCs is required for hippocampal gamma oscillations, supporting a pyramidal-interneuron network gamma model. Phenytoin-mediated modulation of hippocampal gamma oscillations may be a mechanism underlying its anticonvulsant efficacy, as well as its contribution to cognitive impairments in epilepsy patients.